Real-World Experience Treating Pediatric Epilepsy Patients With Cenobamate - Makridis, Konstantin L.; Bast, Thomas; Prager, Christine; Kovacevic-Preradovic, Tatjana; Bittigau, Petra; Mayer, Thomas; Breuer, Eva; Kaindl, Angela M. (Frontiers in Neurology, 2022)
Introduction: In one third of all patients with epilepsy, seizure freedom is not achieved through anti-seizure medication (ASM). These patients have an increased risk of earlier death, poorer cognitive development, and reduced quality of life. Cenobamate (CNB) has recently been approved as a promising novel ASM drug for the treatment of adults with focal-onset epilepsy. However, there is little experience for its application in pediatric patients. Methods: In a multicenter study we evaluated retrospectively the outcome of 14 pediatric patients treated ‘off label’ with CNB. Results: In 16 patients with a mean age of 15.38 years, CNB was started at an age of 15.05 years due to DRE. Prior to initiation of therapy, an average of 10.56 (range 3-20) ASM were prescribed. At initiation, patients were taking 2.63 (range 1-4) ASM. CNB was increased by 0.47 ±0.27mg/kg/d every two weeks with a mean maximum dosage of 3.1 mg/kg/d (range 0.89 – 7) and total daily dose of 182.81 mg (range 50-400 mg). Seizure freedom was achieved in 31.3% and a significant seizure reduction of >50% in 37.5%. Adverse events occurred in ten patients with fatigue/somnolence as the most common. CNB is taken with high adherence in all but three patients with a median follow-up of 168.5 days Conclusion: Cenobamate is an effective ASM for pediatric patients suffering from drug-resistant epilepsy. In addition to excellent seizure reduction or freedom, it is well tolerated. Cenobamate should be considered as a novel treatment for DRE in pediatric patients.